RELATION OF Ca, P AND Mg CONCENTRATIONS IN BLOOD PLASMA OF DAIRY COWS DURING DIFFERENT LENGTH OD OPEN DAYS PERIOD - Ćutuk, Amel; Hrković-Porobija, Amina; Šaljić, Ermin; Velić, Lejla; Čengić, Benjamin; Tandir, Faruk (Works of the Faculty of Agriculture and Food Sciences University of Sarajevo, 2026)
Metabolism in high yield dairy cows considering their genetic predisposition for high milk production from one side and reproductive demands from other is very strained and constantly exposed to changes, which as consequence may have disorders in function of different organ systems, including reproductive system. Minerals play important role in keeping of reproductive potential, as well as maintanence of healthy genital organs in domestic animals. Research had been conducted with 46 Holstein cows in dry period from two farms, 20 cows in farm „A“ and 26 cows in farm „B“. Blood is spectometrically analysed for levels of calcium (Ca), phosphorus (p) and Magnesium (Mg). Obtained average values of Ca, P and Mg in blood were mostly within physiological range, but significant differences could be found among three categories of cows within same or different farms. Higher values of Ca, P and Mg had been found in cows with shorter open days period.